Correlation of Inflammatory Markers, Survival, and COX2 Expression in Oral Cancer and Implications for Prognosis. (April 2018) - Sano, Yoshie; Kogashiwa, Yasunao; Araki, Ryuichiro; Enoki, Yuichiro; Ikeda, Tetsuya; Yoda, Tetsuya; Nakahira, Mitsuhiko; Sugasawa, Masashi
Objective: Peripheral blood–derived inflammation-based scores, such as the neutrophil-lymphocyte ratio (NLR), platelet-lymphocyte ratio (PLR), and the combination of platelet count and NLR, have recently been proposed as prognostic markers in solid tumors. The purpose of this study was to investigate the validity of inflammatory markers as predictive prognostic factors for locally advanced oral squamous cell carcinoma (OSCC). In addition, we evaluated the potential correlation between systemic inflammation and local expression of COX2. Study Design: Retrospective chart review and histologic analysis. Setting: Tertiary referral academic center. Subjects and Methods: We conducted a retrospective analysis of 94 patients with advanced OSCC treated with surgery at our hospital between 2007 and 2015. The relationship among patient survival, systemic inflammatory markers, and local COX2 expression was evaluated. Local COX2 expression in surgical specimens was measured by immunohistochemistry. Results: High NLR and high PLR were associated with significantly shorter overall survival and cancer-specific survival. Multivariate analysis revealed that cN stage, NLR, and postoperative radiation/chemoradiation were significantly associated with overall survival and cancer-specific survival. PLR and combination of platelet count and NLR were significantly correlated with tumor expression of COX2. Finally, patients with cN2 stage disease and high local COX2 expression had a significantly worse prognosis than other patient groups. Conclusion: Pretreatment inflammatory markers are useful as prognostic factors in advanced OSCC. Our study suggests that local COX2 may be affected by systemic inflammation and that the prognostic impact of COX2 expression depends on host factors and tumor characteristics.